The determinants factor on predicting palm oil companies’ stock price listed in Indonesia Stock Exchange - Sri Handayani; Purwanto Purwanto (Proceeding of the International Conference on Family Business and Entrepreneurship, 2022)
Agriculture is a strategic sector in the Indonesian economy where palm oil is the main national export. The research aims to examine the influence of sales growth, net profit margin, earnings per share, return on equity, debt to equity ratio and firm size to stock price with the BI rate as the moderating variable of earnings per share and debt to equity ratio in influences stock price in palm oil companies listed in Indonesian Stock Exchange. This research uses secondary data obtained from financial reports, annual reports, company reports, research journals, and other literature data. The method used for sample selection is purposive sampling. The sample used was 10 palm oil companies listed on the Indonesia Stock Exchange from 2013 to 2020. The analysis method uses EViews 11 and the multiple linear regressions used in this study with the random effect model are chosen. Partially the results of this study indicate that EPS and DER have positive and significant effects on stock prices. Sales growth, NPM, and firm size have positive but not significant effect on stock price, and meanwhile, ROE partially has negative and not significant effect on stock price. Simultaneously sales growth, NPM, EPS, ROE, DER and firm size have significant influence on stock price. The variable BI rate is not able to moderate the influence of earnings per share and debt to equity ratio on stock price in palm oil companies 2013-2020.